Large Rearrangements in Genes Responsible for Familial Adenomatous Polyposis, MUTYH-Associated Polyposis and Peutz–Jeghers Syndrome in Russian Patients - A. N. Loginova; Yu. A. Shelygin; V. P. Shubin; A. M. Kuzminov; D. Yu. Pikunov; T. A. Saveleva; A. S. Tsukanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: to reveal the rate of large rearrangements in the genes responsible for familial adenomatous polyposis, MUTYH-associated polyposis and Peutz–Jeghers syndrome.Materials and methods. The MLPA method was used for identification of large rearrangements. A total number of 135 patients was included in the study: 83 patients with a clinical diagnosis of “familial adenomatous polyposis”, 18 — with suspected MUTYH-associated polyposis, and 34 — with a clinical diagnosis of “Peutz–Jeghers syndrome”.Results. Seven large deletions and one large duplication in the APC gene were identified in 83 patients with classic familial adenomatous polyposis, with rate of large rearrangements 9.6 % (8/83). In 18 patients with suspected MUTYH-associated polyposis, no large rearrangements were found in the MUTYH gene. Four large deletions in the STK11 gene (12 %, 4/34) were detected in 34 patients with Peutz–Jeghers syndrome.Conclusion. For the first time, the expediency of including the method of detecting large rearrangements in routine DNA test list for Russian patients with various hereditary polyposis syndromes is demonstrated. Routine use of MLPA method makes it possible to increase the total frequency of detection of pathogenic variants in the APC and STK11 genes above 90 %. At the same time, the need for searching of large rearrangements in the MUTYH gene were not justified.